Secret on set - LeBlanc, Hayley (Naperville, Ilinois Sourcebooks, 2023)
Thirteen-year-old Hayley has the lead role on a television show about a young detective, but when strange things happen around the studio, she and her friends become real-life sleuths.
Ages 8-12.
Grades 4-6.
112397
Keywords: LeBlanc, Hayley -- Juvenile fiction; Actors and actresses -- Fiction; Television programs -- Fiction; Mystery and detective stories; Actors; Murder; Practical jokes; California -- Los Angeles -- Hollywood; Detective and mystery stories; Children's stories; Fiction; Juvenile works